Modern tennis rackets, balls, and surfaces - Miller, S. (British Journal of Sports Medicine, 2006)
Modern rackets have facilitated a change in playing style from one of technique to one characterised by power and spin. The combination of the increased stiffness of modern rackets and the tendency for tennis balls to have become harder has led to an increased shock transmission from the racket to the player, which is probably a major contributor to tennis elbow. The paucity of tennis specific research on shoes and surfaces makes it difficult to link their characteristics with lower limb injury, although, as their interaction directly affects the magnitude of the forces to which the player is exposed, such a link seems reasonable.